Two poles of height

Asked by hemant2020 | 6th Sep, 2010, 11:40: PM

Expert Answer:

Dear Student,
Consider the following figure:
Applying similar triangles on both the pair of triangles, we get:
a/p = h/x.............(1)
b/p = h/(p-x)...........(2)
Substituting the value of x from equation 1 in equation 2, we get
b/p = h/(p-hp/a)
=> b = ah/(a-h)
=> ab - bh = ah
=> h = ab/(a+b)
Hence Proved
Regards Topperlearning.

Answered by  | 7th Sep, 2010, 11:48: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.